TITHE HISTORY VALUE REACTUALISATION PROMOTING THE EFFICIENTLY IMPLEMENTATION OF ZAKAT MANAGEMENT - Cucu Solihah (Faculty of Law, Universitas Jenderal Soedirman, 2015)
Two dimensions of zakat both religion and social give positive impact to society life, particularly in developing social responsibility. The Islamic history literature hasrecorded with golden ink the management of tithe which managed by the government, resulted the human prosperity which it proved the greatness of Islamic rule and the honor of human. The government has the strategic rule to realize the goal of tithe; Indonesia has the great potential to do it, since the majority of Indonesian peoples is moslem and there is a regulation that regulate it seriously to make the tithe as the potential alternative way to prevent poverty and to prospersociety. Keyword: tithe(zakat), government, poverty, prosperity/welfare